Fish gelatin films incorporated with different oils: effect of thickness on physical and mechanical properties - A. H., Norfarahin; Sanny, Maimunah; Sulaiman, R.; Zainal Abedin, Nur Hanani (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Properties of fish gelatin films incorporated with different oils at different thickness investigated. Gelatin films incorporated with all oils resulted in higher elongation at break (EAB) compared to control film, regardless of the oils type (P≤0.05). Increasing the thickness of gelatin films with oils decreased the solubility value (P≤0.05) significantly. However, water vapor permeability (WVP) of gelatin films containing oils increased as the thickness of films increased. FTIR spectra showed that incorporation of different oils into gelatin films gave effect on the molecular organization and intermolecular interaction in films matrix particularly at the wavenumber of Amide-I band and 1739-1744 cm-1. SEM analysis revealed the addition of oils into gelatin films enhanced the roughness of the film surface and cross-section. An appropriate combination of oils at moderate thickness could improve the mechanical and barrier properties of fish gelatin films thus fulfill the application either as coatings or films.